Public Beliefs about Antibiotics, Infection and Resistance: A Qualitative Study - Helen Madden; Jonathan Gabe; Kerry Chamberlain; Darrin Hodgetts; Kevin Dew; Pauline Norris (MDPI AG, 2013)
We aimed to gain an in-depth understanding of public views and ways of talking about antibiotics. Four focus groups were held with members of the public. In addition, 39 households were recruited and interviews, diaries of medicine taking, diaries of any contact with medication were used to explore understanding and use of medication. Discussions related to antibiotics were identified and analyzed. Participants in this study were worried about adverse effects of antibiotics, particularly for recurrent infections. Some were concerned that antibiotics upset the body's "balance", and many used strategies to try to prevent and treat infections without antibiotics. They rarely used military metaphors about infection (e.g., describing bacteria as invading armies) but instead spoke of clearing infections. They had little understanding of the concept of antibiotic resistance but they thought that over-using antibiotics was unwise because it would reduce their future effectiveness. Previous studies tend to focus on problems such as lack of knowledge, or belief in the curative powers of antibiotics for viral illness, and neglect the concerns that people have about antibiotics, and the fact that many people try to avoid them. We suggest that these concerns about antibiotics form a resource for educating patients, for health promotion and social marketing strategies.